2009
DOI: 10.1186/1471-2180-9-118
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and selection of rpoS in pathogenic Escherichia coli

Abstract: BackgroundThough RpoS is important for survival of pathogenic Escherichia coli in natural environments, polymorphism in the rpoS gene is common. However, the causes of this polymorphism and consequential physiological effects on gene expression in pathogenic strains are not fully understood.ResultsIn this study, we found that growth on non-preferred carbon sources can efficiently select for loss of RpoS in seven of ten representative verocytotoxin-producing E. coli (VTEC) strains. Mutants (Suc++) forming large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 68 publications
5
69
0
Order By: Relevance
“…Of these 15 substrates inducing responses measured by the Biolog assay, the increased responses with L-serine and L-threonine correspond well with the increase in expression of tdcCA, genes involved in both L-threonine and L-serine uptake. Increased utilization of succinic acid (succinate) by RM6069 and RM9998 also is consistent with the SPANC hypothesis and the ability to select rpoS mutants on succinate minimal medium (14).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Of these 15 substrates inducing responses measured by the Biolog assay, the increased responses with L-serine and L-threonine correspond well with the increase in expression of tdcCA, genes involved in both L-threonine and L-serine uptake. Increased utilization of succinic acid (succinate) by RM6069 and RM9998 also is consistent with the SPANC hypothesis and the ability to select rpoS mutants on succinate minimal medium (14).…”
Section: Resultssupporting
confidence: 69%
“…A relevant part of the hypothesis specifically suggests that competition between S and 70 defines the gene expression and phenotypes exhibited by the bacteria (22). In fact, rpoS mutants have been selected for by growth on nonpreferred carbon sources (14). Here, we demonstrated that the clinical and spinach isolates with mutations within rpoS and/or with decreased levels of S exhibited decreased expression of stress-related genes (see Table S1 in the supplemental material) and lower resistance to acid, high-salt conditions, and oxidation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive mutations within the rpoS gene are selected in laboratory and pathogenic E. coli strains in nutrient-poor conditions or during growth on nonpreferred carbon sources (13,17,61,84). Because E. coli can be found in a wide range of environments (10,34,56), including putative poor carbon environments, we postulated that RpoS mutants are present, and may be selected, in environmental E. coli populations.…”
mentioning
confidence: 99%
“…A similar role was proposed also for natural RpoS-inactivating mutations (50). However, in the in-host environment, stress and nutritional competition appear to be equally important, in that different types of mutations, i.e., loss-of-function mutations and those affecting the expression level of RpoS, are selected (51)(52)(53). Interestingly, virulence analysis of different clonally related E. coli isolates from the same patient with distinct RpoS expression levels showed that a lower level of RpoS was strongly associated with better growth in vitro and greater virulence in the murine septicemia model (51).…”
Section: Discussionmentioning
confidence: 99%